Targeting LRP6: A new strategy for cancer therapy - Wei Xue; Bo Zhu; Kaili Zhao; Qiuju Huang; Hua Luo; Yiwen Shou; Zhaoquan Huang; Hongwei Guo (Elsevier, 2024)
Targeting specific molecular drivers of tumor growth is a key approach in cancer therapy. Among these targets, the low-density lipoprotein receptor-related protein 6 (LRP6), a vital component of the Wnt signaling pathway, has emerged as an intriguing candidate. As a cell-surface receptor and vital co-receptor, LRP6 is frequently overexpressed in various cancer types, implicating its pivotal role in driving tumor progression. The pursuit of LRP6 as a target for cancer treatment has gained substantial traction, offering a promising avenue for therapeutic intervention. Here, this comprehensive review explores recent breakthroughs in our understanding of LRP6's functions and underlying molecular mechanisms, providing a profound discussion of its involvement in cancer pathogenesis and drug resistance. Importantly, we go beyond discussing LRP6's role in cancer by discussing diverse potential therapeutic approaches targeting this enigmatic protein. These approaches encompass a wide spectrum, including pharmacological agents, natural compounds, non-coding RNAs, epigenetic factors, proteins, and peptides that modulate LRP6 expression or disrupt its interactions. In addition, also discussed the challenges associated with developing LRP6 inhibitors and their advantages over Wnt inhibitors, as well as the drugs that have entered phase II clinical trials. By shedding light on these innovative strategies, we aim to underscore LRP6's significance as a valuable and multifaceted target for cancer treatment, igniting enthusiasm for further research and facilitating translation into clinical applications.